Great Depression in literature and visual arts - Vegešová, Kristýna (Univerzita Pardubice, 2021)
This bachelor thesis inspects the events of the Great Depression and the Dust Bowl and also the art of the 1930s in America, focusing on American Regionalism and documentary photography. This paper attempts to show how the crisis influenced the American art of the 1930s and how the Great Depression was depicted. The main focus is on Grant Wood and Thomas Hart Benton as the representatives of American Regionalism and on Dorothea Lange and Marion Post Wolcott as the representatives of documentary photography.
Velká hospodářská krize v literatuře a vizuálním umění
Keywords: Velká hospodářská krize; prachové bouře; Nový úděl; umění; 30. léta; Wood, Grant; Benton, Thomas Hart; Lange, Dorothea; Post Wolcott, Marion; Great Depression; Dust Bowl; New Deal; art; the 1930s; Wood, Grant; Benton, Thomas Hart; Lange, Dorothea; Post Wolcott, Marion